Manifestations of Globalization in International Television Advertising Analytical Study of Ads in MBC1 Channel For the Period from 1/1/2019 TO 31/3/2019 - Shaheed Hashim, Jaafar (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The research aims to provide accurate scientific perceptions on the nature of the role played by the declaration as a means of globalization implement its entitlements and transmit information to the public. The researcher adopted the survey methodology to study the subject of globalization in the international TV advertising through MBC1 channel. It is concluded that the channel, through broadcasting advertisements that promote foreign goods and commodities, has contributed to the consolidation of ways and lifestyles by showing foreign products consumed by foreigners to achieve the desire of the Arab public to reincarnate in foreign life.